Indonesian Air Defense Strategy in Maintaining Airspace Security of The Nusantara Capital City - Sadjuri, Choirul Anam; Dermawan, Windy; Djuyandi, Yusa (International Journal of Science and Society, 2025)
The air defense in the development of the Nusantara Capital City is one aspect that needs serious attention to support airspace security from various threats that could disrupt stability. The Indonesian Air Force has a strategic role in safeguarding the national airspace. However, in efforts to build air defense at the IKN, there are still various issues to address, hence a measured strategy is needed to realize the expected air defense system. This thesis research method used a qualitative paradigm with a descriptive approach. Technically, data was collected through interviews and literature or document studies as well as constructing relationships between the resulting data categories. The research findings indicate that the potential threats in the IKN airspace are very complex. Starting from the Air Defense Identification Zone (ADIZ) is not yet established in the IKN, which increases vulnerability to air threats, and there is still a high incidence of airspace violations in that area. The author analyzes the gap in Indonesia's air defense strategy capabilities through the DOTMLPF-P (Doctrine, Organization, Training, Material, Leadership and Education, Personnel, Facilities, Policy) indicators. Therefore, an integrated air defense system is needed with integration and combination of material elements, as follows multi-spectrum air defense radar, C2 (Command and Control) systems, fighter aircraft, air defense missiles, Indonesian warships with air defense capability, anti-missile systems, anti-drone and supported by air defense facilities and also non-material elements, as follows Doctrine, Organization, Training, Leadership and Education, Personnel and also Policy so that Indonesia can develop a strong and effective air defense strategy to maintain the security of IKN air space.